IAMSAR manual international aeronautical and maritime search and rescue manual. (International Maritime Organization ; International Civil Aviation Organization, 2019)
"The Mobile facilities volume is intended to be carried on board rescue units, aircraft and vessels to help with performance of a search, rescue or on-scene coordinator function and with aspects of search and rescue that pertain to their own emergencies."--Back cover.